The promise of space - Clarke, Arthur C. (Harper & Row, 1968)
Contents: In this immensely informative and exciting book, Arthur C. Clarke opens wide the doors to the fantantis space world of tomorrow -all based on completely feasible advances in the knowledge and equipment of today. He has achieved a mind-expanding triumph-a work that reveals in all its wonder the vast challenge of space and its infinite promise for man